Guide for Drug Selection During Pregnancy and Lactation: What Pharmacists Need to Know for Current Practice. Issue 8 (August 2018) - Griffin, Brooke L.; Stone, Rebecca H.; El-Ibiary, Shareen Y.; Westberg, Sarah; Shealy, Kayce; Forinash, Alicia; Yancey, Abigail; Vest, Kathleen; Karaoui, Lamis R.; Rafie, Sally; Horlen, Cheryl; Lodise, Nicole; et al.
Objective: To provide guidance for clinicians on risk assessment of medication use during pregnancy and lactation.Data Sources: Authors completed PubMed searches to identify articles focused on the use of medications in pregnancy, including fetal development, drug transfer across the placenta, trimester exposure, chronic conditions in pregnancy, medications in lactation, and lactation and chronic disease.Study Selection and Data Extraction: Articles were reviewed to provide overall guidance to medication selection during pregnancy. The following information was reviewed: medication use in pregnancy, including fetal development, drug transfer across the placenta, trimester exposure, chronic conditions in pregnancy, medications in lactation, and lactation and chronic disease.Data Synthesis: This article will provide an overview of medication safety considerations during pregnancy and lactation. Information was interpreted to help clinicians predict the potential risk and benefit in each patient to make an evidence-based decision. The article concludes with guidance on risk assessment and how pharmacists may support fellow health care providers and their patients when considering medication use.Conclusions: Information about the effects of medication use during reproductive periods is limited. With the removal of the Food and Drug Administration pregnancy categories, clinicians will be relying on pharmacists to aid in the appropriate selection of therapies for patients. It is critical that pharmacists keep abreast of resources available and be able to assess data to help prescribers and their patients.